The effect of the antibiotic stewardship program (ASP) on community-acquired pneumonia (CAP): a before–after study - Fésüs, Adina; Baluku, Phiona; Sipos, Éva; Somodi, Sándor; Berczi-Kun, Enikő; Lekli, István; Bácskay, Ildikó; Benkő, Ria; Vaskó, Attila (Frontiers in Pharmacology, 2024)
Background: Community-acquired pneumonia (CAP) is still one of the leading causes of death worldwide. Implementation of the Antibiotic Stewardship Program (ASP) aimed to improve the correct and responsible antibiotic use by encouraging guideline adherence. Objective: This retrospective observational before-after study aimed to evaluate whether the ASP may improve guideline adherence, antibiotic exposure and clinical outcomes in patients hospitalized with CAP in Hungary. Methods:The study was conducted at a Pulmonology Department of a tertiary care medical centre in Hungary. The ASP implementation consisted of written and published guidelines available to all professionals, continuous supervision and counselling service on antibiotic therapies at an individual level, with the aim to ensure compliance with CAP guidelines. Overall guideline adherence (agent selection, route of administration, dose), clinical outcomes (length of stay, 30-day mortality), antibiotic exposure and direct costs were compared between the two periods. Fisher's exact test and t-test were applied to compare categorical and continuous variables, respectively. Results: Significant p values were defined as below 0.05. Significant improvement in overall CAP guideline adherence (30.2%), sequential therapy (10.5%) and significant reduction in the total duration of antibiotic therapy (13.5%) were observed. Guideline non-adherent combination therapies with metronidazole decreased significantly by 28.1%. Antibiotic exposure decreased by 7.2% leading to a significant decrease of direct costs (23.6%). Moreover, ASP had benefits on clinical outcomes, length of stay decreased by 13.5% and 30day survival increased by 5.9%. Conclusion: ASP may play an important role in optimizing empirical antibiotic therapy in CAP having a sustained long-term effect.